Perioperative albumin ratio is associated with post‐operative pancreatic fistula. Issue 7 (30th November 2017) - Gruppo, Mario; Angriman, Imerio; Martella, Bruno; Spolverato, Ylenia C.; Zingales, Francesca; Bardini, Romeo
Abstract : Background: Despite improvements in surgical techniques and perioperative management, post‐operative pancreatic fistula (POPF) remains a serious complication after pancreaticoduodenectomy (PD). The aim of this study was to evaluate the role of perioperative clinical variables of patients, including albumin level, in predicting pancreatic fistula. Methods: A total of 86 patients underwent PD for pancreas cancer between 2011 and 2017 at our institution. We prospectively investigated the relation between patient's characteristics and the incidence of clinically relevant (CR)‐POPF. Perioperative albumin ratio was defined as post‐operative day 1 (POD1) albumin level/preoperative albumin level. Results: A total of 23 patients (26.7%) developed CR‐POPF. At univariate analysis POPF correlated with soft pancreas ( P = 0.045), low POD1 albumin ( P = 0.02), POD1 and POD3 amylase levels in drainage fluid ( P = 0.003 and P = 0.014, respectively) and perioperative albumin ratio (0.58 ± 0.10 versus 0.69 ± 0.12 in patients without POPF; P = 0.003). No significant correlations with POPF were demonstrated for surgical time, serum amylase levels and preoperative albumin levels. At multivariate analysis POD3 amylase level in drainage fluid and perioperative albumin ratio were the only significant independent parameters ( P = 0.027 and P = 0.047, respectively). Conclusions: Perioperative albumin ratio can predict POPF after PD.